2017
DOI: 10.1093/ckj/sfx048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kidney donor hepatitis C virus serostatus on renal transplant recipient and allograft outcomes

Abstract: BackgroundHepatitis C virus (HCV) infection is common in dialysis patients and renal transplant recipients and has been associated with diminished patient and allograft survival. HCV-positive (HCV+) kidneys have been used in HCV-positive (HCV+) recipients as a means of facilitating transplantation and expanding the organ donor pool; however, the effect of donor HCV serostatus in the modern era is unknown.MethodsUsing national transplant registry data, we created a propensity score–matched cohort of HCV+ recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Discard of HCV-positive kidneys and livers might be warranted in certain circumstances; some studies of HCV-positive recipients have shown worse posttransplant outcomes with HCV-positive versus HCV-negative kidneys and livers (13, 14). However, studies have shown that patients who accept HCV-positive organs have reduced wait times (14) and outcomes similar to those with HCV-negative organs (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discard of HCV-positive kidneys and livers might be warranted in certain circumstances; some studies of HCV-positive recipients have shown worse posttransplant outcomes with HCV-positive versus HCV-negative kidneys and livers (13, 14). However, studies have shown that patients who accept HCV-positive organs have reduced wait times (14) and outcomes similar to those with HCV-negative organs (34).…”
Section: Discussionmentioning
confidence: 99%
“…The IRD label might reduce use of ODD organs because it is associated with organ discard (surgical recovery without subsequent use for transplant) (12). Moreover, ODDs are increasingly positive for HCV antibodies (10, 11), and inferior outcomes might be expected due to HCV infection (1316). Finally, concerns that illicit drug use compromises organ quality might exist; for example, injection drug use is associated with lung granulomatosis (17).…”
mentioning
confidence: 99%
“…Chronic kidney disease is a common extrahepatic manifestation associated with HCV‐induced cryoglobulinemia vasculitis . While kidney transplant outcomes from HCV‐positive donors have been reported to be inferior to transplants performed using HCV‐negative donors, acceptance of HCV antibody‐positive donors significantly shortens transplant candidate waiting times . Similar or favorable transplant outcomes are reported among HCV‐positive recipients who accepted HCV‐positive donor grafts compared to those who remained on the wait list longer and received HCV‐negative grafts …”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, HCV infection in heart transplant recipients has been associated with liver failure, renal dysfunction, CAV, and increased mortality after transplant compared to non‐HCV organs . Additionally, in renal transplant, recipients with active HCV have an increased risk of death and allograft loss . Thus, this potential donor pool has been largely underutilized.…”
Section: Discussionmentioning
confidence: 99%